Single-Atom Cobalt-Based Electrochemical Biomimetic Uric Acid Sensor with Wide Linear Range and Ultralow Detection Limit - Hu, Fang Xin; Hu, Tao; Chen, Shihong; Wang, Dongping; Rao, Qianghai; Liu, Yuhang; Dai, Fangyin; Guo, Chunxian; Yang, Hong Bin; Li, Chang Ming (Nano-Micro Letters, 2020)
Uric acid (UA) detection is essential in diagnosis of arthritis, preeclampsia, renal disorder, and cardiovascular diseases, but it is very challenging to realize the required wide detection range and low detection limit. We present here a single-atom catalyst consisting of Co(II) atoms coordinated by an average of 3.4 N atoms on an N-doped graphene matrix (A–Co–NG) to build an electrochemical biomimetic sensor for UA detection. The A–Co–NG sensor achieves a wide detection range over 0.4–41,950 μM and an extremely low detection limit of 33.3 ± 0.024 nM, which are much better than previously reported sensors based on various nanostructured materials. Besides, the A–Co–NG sensor also demonstrates its accurate serum diagnosis for UA for its practical application. Combination of experimental and theoretical calculation discovers that the catalytic process of the A–Co–NG toward UA starts from the oxidation of Co species to form a Co3+–OH–UA*, followed by the generation of Co3+–OH + *UA_H, eventually leading to N–H bond dissociation for the formation of oxidized UA molecule and reduction of oxidized Co3+ to Co2+ for the regenerated A–Co–NG. This work provides a promising material to realize UA detection with wide detection range and low detection limit to meet the practical diagnosis requirements, and the proposed sensing mechanism sheds light on fundamental insights for guiding exploration of other biosensing processes. Highlights: 1 A single-atom catalyst of A–Co–NG is explored for electrochemical uric acid (UA) detection for the first time and realize practical UA monitoring in serum samples. 2 The A–Co–NG sensor demonstrates high performance for UA detection with a wide detection range from 0.4 to 41950 μM and an extremely low detection limit of 33.3 nM. 3 Combination of experimental and theoretical calculation discovers mechanism for the UA oxidation on the single-atom catalyst.